The Legitimacy of Profit of Microlending Institutions and Women’s Empowerment: A Case Study from Jordan - Nebal Al Maaitah (Theory, Methodology, Practice, 2019)
The aim of this paper is to investigate the impact of the profitability policy of microlending institutions on women’s social empowerment in specific aspects (education, health, and social status). Data were collected from 385 women-led microenterprises in Jordan. The dependent variable will be social empowerment measured by education, health, and social status. Descriptive analysis and regression analysis findings revealed there is no impact of profitability policy on women’s level of education, social status and the whole dimension of social empowerment. However, there is a positive effect of profitability on women’s health. This paper gives recommendations to policy makers to reformulate the current profitability policy to further support the global goal of women empowerment, and reflect the microcredit ideology.